Morphology, Diet, and Temperature-Dependent Host-Free Survival of the Boll Weevil, Anthonomus grandis (Coleoptera: Curculionidae). Issue 3 (29th May 2018) - Spurgeon, Dale W; Suh, Charles P -C
Abstract: The boll weevil, Anthonomus grandis grandis Boheman (Coleoptera: Curculionidae), is an important pest of cotton ( Gossypium spp. (Malvales: Malvaceae)) in South America, Mexico, and southernmost Texas in the United States. A key factor in the persistence of the boll weevil is its ability to survive the noncotton season. Mechanisms facilitating this survival in subtropical and tropical areas are incompletely known, and our understanding has been further complicated by recent reports of overwintering on noncotton hosts. In addition, the nature and even existence of the adult dormancy, and validity of the criteria used to distinguish it, have been questioned. We manipulated the boll weevil diet to produce a range of diapause responses and observed the corresponding host-free survival patterns. The estimated proportion of diapause was associated with subsequent survival. In addition, different diets producing similar incidences of diapause resulted in substantially different host-free longevity, and the longest survival was observed for weevils fed bolls as adults. Survival patterns exhibited a negative temperature dependence except for the lowest observed temperature (12.8°C), where survival was reduced compared with that at 18.3°C. This suggests chronic chilling injury in response to extended exposure to low, above freezing temperatures. All but the highest temperature (29.4°C) facilitated survival >6 mo, and survival of >1 yr was observed at 18.3°C. The temperatures permitting the greatest survival are typical for many subtropical and tropical regions during the noncotton season, indicating that diapausing boll weevils are capable of surviving the noncotton season in these regions without the benefit of presumptive noncotton hosts.